Size and light absorption of miniature-inverted-soot-generator particles during operation with various fuel mixtures. (May 2023) - Senaratne, Amrith; Olfert, Jason; Smallwood, Greg; Liu, Fengshan; Lobo, Prem; Corbin, Joel C.
Abstract: The Argonaut miniature inverted soot generator (MISG) serves as a convenient and stable source of soot black-carbon aerosol particles. The MISG performance has been previously characterized for ethylene and propane, in a simple two-flow setup of fuel and air. These fuels produce soot size distributions with geometric median diameters (GMDs) of 150–200 nm. These sizes are substantially larger than the soot particles emitted from typical internal-combustion and aviation gas turbine engines. Here, we sought to produce substantially smaller soot particles, representative of aviation gas turbine engine emissions, by using five different fuels (acetylene, methane, ethylene, propane, and dimethyl ether) and by enriching the combustion air with oxygen. We developed a rapid screening protocol for each fuel, to allow the full range of stable flame conditions to be explored. We monitored the size distribution, mass concentration, and mass absorption cross section (MAC) of denuded MISG soot in real time. We considered only operating conditions where stable soot mass concentrations above 3 μg/m 3 were emitted, corresponding to a non-flickering and open-tipped flame. For virtually all operating conditions, the measured MAC was consistent with literature values for mature soot. The only exception was a propane-acetylene mixture, for which the measured MAC was much lower than literature values. The observed GMDs fell into two groups, and we did not identify any trends leading to the mixtures falling into either group. The two groups were at approximately 100 nm and 160 nm. Therefore, while this study identified conditions that reduced the soot particles to 100 nm, it did not identify conditions where even smaller soot particles could be produced. This study has demonstrated that the soot properties produced by the MISG are highly repeatable and relatively insensitive to fuel composition. Highlights: An Argonaut miniature inverted soot generator was operated with various fuels, and with oxygen-enriched air. For all combustion mixtures, the mode soot-particle size produced at substantial concentrations was 100 nm–160 nm mobility diameter. In all cases, the soot mass-absorption cross-section (MAC) was not significantly different from the expected value of 8.0 m 2 /g at 550 nm.